The Socio-Demographic and Innovative Behavior in University Employee: Evidence From West Kalimantan Province - Syarif Zulkifli; Rizky Fauzan; Ilzar Daud (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Digital disruption demands innovation in higher education, making employee innovative behavior vital to institutional adaptation. Limited research has explored how demographic characteristics affect innovative behavior in Indonesian higher education. West Kalimantan was selected due to its six state universities undergoing institutional transformation, providing ideal context for examining innovative behavior during organizational change.Purpose: This research examines differences in idea generation dimension of innovative behavior between faculty with additional duties and educational staff at state universities in West Kalimantan, based on income, education level, work tenure, and age.Design/methodology/approach: This quantitative research used online questionnaire adapted from De Jong and Den Hartog's (2007) instrument with 5-point Likert scale, distributed to 300 respondents comprising 78 faculty with additional duties and 222 educational staff. Cross-tabulation with Chi-Square test examined associations between demographic characteristics and innovative behavior.Findings/Result: Chi-Square analysis revealed significant associations between demographic characteristics and innovative behavior. Among faculty, higher income showed significant association with innovative behavior, with highest scores above 10 million Rupiah. Longer tenure contributed significantly to proposing new methods. Conversely, educational staff demonstrated declining innovative behavior with increasing tenure and age. Notable finding is non-linear relationship between education and innovative behavior, where staff with high school education showed comparable scores to diploma/bachelor holders.Conclusion: Demographic characteristics influence innovative behavior differently between faculty and educational staff. Institutions should develop differentiated approaches for specific demographic groups and leverage high-performing segments as change agents. These findings provide practical implications adaptable by other institutions facing similar transformation challenges.Originality/value: This study comparatively examines how demographic characteristics influence innovative behavior between faculty and educational staff in Indonesian context, supported by Chi-Square analysis. Identified patterns offer transferable insights for universities undergoing reform and digital transformation. Keywords: demographic characteristic, human resource management, innovative behavior, higher education, socio-demographic